Adaptability of free-floating green tide algae in the Yellow Sea to variable temperature and light intensity. Issue 2 (30th December 2015) - Cui, Jianjun; Zhang, Jianheng; Huo, Yuanzi; Zhou, Lingjie; Wu, Qing; Chen, Liping; Yu, Kefeng; He, Peimin
Abstract: In this study, the influence of temperature and light intensity on the growth of seedlings and adults of four species of green tide algae ( Ulva prolifera, Ulva compressa, Ulva flexuosa and Ulva linza ) from the Yellow Sea was evaluated. The results indicated that the specific growth rate (SGR) of seedlings was much higher than that of adults for the four species. The adaptability of U. prolifera is much wider: Adult daily SGRs were the highest among the four species at 15–20 °C with 10–600 μmol·m − 2 ·s − 1 and 25–30 °C with 200–600 μmol·m − 2 ·s − 1 . SGRs were 1.5–3.5 times greater than the other three species at 15–25 °C with 200–600 μmol·m − 2 ·s − 1 . These results indicate that U. prolifera has better tolerance to high temperature and light intensity than the other three species, which may in part explain why only U. prolifera undergoes large-scale outbreaks and floats to the Qingdao coast while the other three species decline and disappear at the early stage of blooming. Highlights: The adaptability of four species of green algae in the Yellow Sea to variable temperature and light intensity was analyzed. The optimal combinations of temperature and light intensity for the four species of green tide algae were measured. U . prolifera has wider adaptability for high temperature and light intensity, explaining its dominance in the Yellow Sea.